2019
DOI: 10.1186/s13104-019-4669-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human norovirus binding to gut-associated bacterial ligands

Abstract: Objective Research suggests human norovirus binding to histo-blood group antigen (HBGA)-like molecules on enteric bacteria may enhance viral pathogenesis; however, the properties of these bacterial ligands are not well known. Previous work identified, but did not characterize, seven norovirus-binding bacteria. To further examine this bacteria–virus binding interaction, enteric bacteria were analyzed via Western blot with anti-HBGA antibodies and lectins targeting HBGA-associated sugar component… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Some probiotic and commensal gut bacteria have the ability to in vitro bind RV and human noroviruses [12][13][14][15], and HBGA-like substances have been detected on the surface of enteric species such as Enterobacter cloacae [13], Enterobacter faecium, Klebsiella spp., Citrobacter spp. and Hafnia alvei [16]. The bacterium E. cloacae enhanced norovirus infectivity in gnotobiotic mice and in an in vitro model of infection in human B cells [10].…”
Section: Introductionmentioning
confidence: 98%
“…Some probiotic and commensal gut bacteria have the ability to in vitro bind RV and human noroviruses [12][13][14][15], and HBGA-like substances have been detected on the surface of enteric species such as Enterobacter cloacae [13], Enterobacter faecium, Klebsiella spp., Citrobacter spp. and Hafnia alvei [16]. The bacterium E. cloacae enhanced norovirus infectivity in gnotobiotic mice and in an in vitro model of infection in human B cells [10].…”
Section: Introductionmentioning
confidence: 98%
“…The protective effect of human gut microbiota could also be involved because it has recently been shown that some enteric bacteria (e.g. Enterobacter cloacae ) bind HuNoVs through the H-like carbohydrates present on the bacterial surface 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…HBGAs as receptors for HuNoVs can also be further described by the fact that HBGA-expressing bacteria can aid in the cultivation of HuNoVs in a B cell line [32]. In addition, different NoV strains have variable binding abilities to HBGA-expressing bacteria [32][33][34]. Even though almost all HuNoVs bind to HBGAs, some strains of GI VLPs, GII.1 VLPs and GII.14 VLP do not bind to any type of HBGAs nor any saliva [28,35].…”
Section: Introductionmentioning
confidence: 99%